Evaluation of total hydroxytyrosol and tyrosol in extra virgin olive oils. Issue 7 (14th April 2014) - Purcaro, Giorgia; Codony, Rafael; Pizzale, Lorena; Mariani, Carlo; Conte, Lanfranco
<x xml:space="preserve">Abstract</x> Olive oil phenolic compounds have been correlated to several health benefits. Nevertheless, the use of such information for commercial purposes was forbidden until 2006, when a European Regulation on health claims in food products was enacted (Reg. 1924/2006). In the case of olive oil, Regulation 432/2012 states that the health effect can be claimed only if the oil contains more than 5 mg of hydroxytyrosol and its derivatives (e.g., oleuropein complex and tyrosol) in 20 g of oil. The present work deals with the optimization of a method for performing hydrolysis after the extraction of polyphenols from olive oil was optimized, followed by derivatization and gas chromatographic analysis. The derivatization step was carefully optimized comparing different reagents and testing their efficiency, both on a standard solution and in a real sample conveniently spiked. Some commercial samples were analyzed and the results compared with the total amount of polyphenols calculated according the recommended method reported by the International Olive Council. A good correlation was obtained between the two methods (higher than 0.900). Practical applications: The proposed method is useful to determine if a marketed oil can claim health benefit according to the European Regulation n. 432/2012. The possibility to use such a claim is very important from a marketing point of view for the olive oil company; however, at present there is not any official method to assess the requirements. This method is rapid and gives efficient and reliable results using a common GC‐FID for the final determination. <inline-graphic xlink:href="ark:/27927/pghntzxh81" content-type="ejlt201300420-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> A GC method to evaluate European health claim requirements related to polyphenol contents in olive oil.